Recent Advances in H2S Removal from Gas Streams - Francisco Jose Alguacil (Applied Sciences, 2023)
Hydrogen sulfide is a toxic and corrosive gas; thus, in order to mitigate its environmental impact, its capture and removal from various emitting sources, natural and anthropogenic, is of a necessity. In this work, recent advances (2020–2022) proposed by a series of investigations are reviewed. Adsorption using metal-oxide-based adsorbents appeared to be the most popular technology, whereas solvent absorption is used to co-absorb both toxic H2S and CO2. The uses of the various membrane technologies for H2S removal are also described.